Comparison of COVID-19 Antigen Test and HRCT Chest with RT- PCR Test for Diagnosis of COVID-19 - Ghimire, Pukar; Bhandari, Isha; Bhandari, Rajan; Bhandari, Bibek (Journal of College of Medical Sciences-Nepal, 2021)
Introduction: We aim to compare Rapid Antigen Test and HRCT chest with Reverse Transcriptase-Polymerase chain reaction (RT-PCR) for diagnosis of COVID-19. Methods: This was a cross-sectional analytical study that included patients tested with RT-PCR and at least one of Rapid Antigen test or HRCT chest, conducted at College of Medical Sciences, Bharatpur, from June 2020 to Feb 2021 after obtaining the ethical clearance. Data analysis was done using statistical packages for social sciences version 16. Results: 315 of 755(41.7%) patients had positive RT-PCR and 18.4% of 733 patients had positive antigen test. Of 600 patients, 106(14.0%) were found to have CO-RADS 1,152(20.1%) had CO-RADS 2, 77(10.2%) had CO-RADS 3, 18(2.4%) had CO-RADS 4 and 247(32.7%) had CO-RADS 5 score on HRCT. Rapid Antigen Test was found to have 43.6% sensitivity, 98.6% specificity, 95.6% Positive predictive value (PPV) and 72.1% negative predictive value (NPV).CO-RADS scoring system was able to distinguish between RT-PCR positive and RT-PCR negative results with an average Area under curve 0.787. CO-RADS 5 had a sensitivity of 71.6%, specificity of 85.1%, PPV of 80.6% and NPV of 77.6% for a positive RT-PCR result. A combination of CO-RADS 1 in HRCT chest and Negative Antigen test can predict PCR negative result with 23.6% sensitivity, 97.3% specificity, 90.5% PPV and 54.0% NPV. Conclusions: Rapid Antigen Test is a better tool for confirmation rather than screening of COVID-19. HRCT chest with higher CO-RADS can be useful to diagnose COVID-19 in suspected patients, even if RT-PCR is negative.